Relationship Between Morphological Change of Median Nerve and Clinical Outcome Before and After Open Carpal Tunnel Release: Ultrasonographic 1-Year Follow-up After Operation. (May 2022) - Tajika, Tsuyoshi; Kuboi, Takuro; Endo, Fumitaka; Chikuda, Hirotaka
Background: The aims of this study were 2-fold: (1) to assess the morphological change of the median nerve in patients with carpal tunnel syndrome (CTS) preoperatively and at 6 and 12 months postoperatively; and (2) to analyze correlation between the changes in ultrasonographic findings and the changes in clinical findings after surgical decompression.Methods: Of the 28 patients with CTS, 34 wrists were treated with open carpal tunnel release. We evaluated them using the Boston questionnaire, Japanese Society for Surgery of the Hand Version of the Quick Disability of the Arm, Shoulder, and Hand questionnaire, nerve conduction study (NCS), and ultrasound preoperatively and at 6 and 12 months postoperatively. We measured the cross-sectional area (CSA) of the median nerve at the level of the proximal inlet of the carpal tunnel (CSAc) and more proximally at the level of the distal radioulnar joint (CSAd). Paired t tests and repeated measures analysis of variance of ranks were used to identify changes over time. The Spearman correlation coefficient by rank test was used for the analysis of the relation between the amount of change of CSA and the patient-rated questionnaire score and NCS findings.Results: Findings for CSAc, CSAd, and NCS and patient-rated outcomes at 6 and 12 months postoperatively were significantly lower than their preoperative values. However, no significant correlation was found between the postoperative changes in CSAc, CSAd, and clinical variables obtained preoperatively and postoperatively.Conclusions: Evaluation of sonographic imaging might not be helpful for assessing clinical conditions in patients with CTS after surgical decompression.